Ageing Well Public Talks Series 2024-2025 Talk 8 - Evidence based actions supporting better mental wellbeing for all. ACCESSIBLE - Charlotte Jack (20985878) (2025)
In this talk, Charlotte and Nicola will explore the support Turning Point UK in Warwickshire offers to ageing populations with learning disabilities in terms of building confidence, getting out and about, accessing community, socialisation, and learning while ageing. Charlotte Jack is a Wellbeing and Community Navigator at the charity Turning Point in Warwickshire Wellbeing team - Charity Turning Point. While starting her career in social care, empowering and promoting independence for individuals with a learning disability who struggle to have a voice. She also has a keen interest in modern Feminism and the effect it has on the world today. Nicola Hopkins is the manager of The Warwickshire Wellbeing Service, which is a part of the charity Turning Point. Nicola has over 20 years experience working within Health and Social Care, Learning Disability sector. Nicola's career started as a community day service support worker with the NHS. She would later move to Turning Point and continue as an LD support worker, and later become a Moving and Handling Trainer. Nicola has had to challenge inequalities for the people that she supports on many occasions.